The Influence of Digital Banking Services (E-Chanel) on Customer Loyalty of PT Bank Central Asia Jakarta Branch - Arsj, Febri Rakhmawati (ProBisnis : Jurnal Manajemen, 2024)
Banking institutions play a crucial role in the economy by enabling resource allocation and credit provision, with Bank Indonesia focusing on monetary stability. This study explores how digital banking services affect customer loyalty at PT Bank Central Asia (BCA). A quantitative approach was adopted, utilizing SPSS Statistics 23 for data analysis from a sample of 100 BCA customers using digital banking services. The findings reveal that digital banking services significantly and positively impact customer loyalty, both individually and simultaneously. This research emphasizes the importance of efficient digital banking services in maintaining customer loyalty.